A Self-Testing Guide to the Bony Features of the Temporal Bone - Bob Hutchins (Association of American Medical Colleges, 2010)
Abstract This interactive temporal bone self-testing guide is expected to be used by novice dental or medical students learning the anatomy of the temporal bone as it relates to the convoluted nerves that pass through the bone, muscle attachments, and middle and inner ear mechanisms. Temporal bone anatomy is traditionally difficult for students to learn and few texts or atlases provide a close up view of this bone's intricate features. Lesions due to trauma, inflammation, or tumors in any part of this bone lead to clinical issues from vertigo, hearing impairment, autonomic disturbances, gustatory disorders, and more. The temporal bone module is divided into four parts; the first part provides an overview of the educational objectives. The second part gives a brief introduction on how to use this module. This is followed by an interactive table of contents and the final part is the actual bony features. The temporal bone presentation is provided anatomically first by presenting external views followed by internal views. This PowerPoint-based aid is used to supplement either traditional gross anatomy and/or neuroscience course material, as well as support case-based learning approaches. The software was tested with first-year dental students to improve the number of structures identified, their presentation, and ease of use. So far, the survey results from those using the module have been significantly in favor of using the module to learn/review the anatomy.